Analysis of cryptographic providers usage in the TLS Protocol - Telnova, A.A.; Balagura, D.S.; Frolenko, V.O.; Sukhoteplyi, V.M.; Florov, S.V. (Radiotekhnika, 2025)
The relevance of this work lies in the need to identify optimal implementations of cryptographic protocols depending on the conditions under which the TLS protocol is used. It is known that the TLS is utilized in various software products, across different platforms and operating systems. Therefore, it is not always feasible to rely on a single cryptographic provider or library to perform cryptographic operations and manage keys. The goal of this study is to analyze the efficiency of cryptographic providers in the TLS protocol and to identify the features that influence their selection and usage based on specific implementation environments and protocol operation aspects. As part of the research, a comparative analysis was conducted on cryptographic provider implementations, including OpenSSL, BoringSSL, and various versions of CryptoAPI. Based on the results of the analysis, recommendations were formulated on the feasibility of using certain cryptographic providers in TLS implementations.